CENTRAL ASIA: PORTRAIT AGAINST THE BACKGROUND OF THE WORLD ECONOMY - KHACHIEV, Georgy (CENTRAL ASIA AND THE CAUCASUS, 2006)
After the breakup of the U.S.S.R. and the formation of five independent states in the part of its territory now called Central Asia,1 this region has assumed great importance not only in the system of international relations, but also in the world economy. The interest taken in Central Asia by the major powers is due in large part to economic factors: its vast area, diverse natural wealth, developed key branches of material production, and advantageous location in the path of transit of goods and services between Europe and the Far East and between North and South Asia. In terms of many parameters of their natural resource and production potential, the republics of the region have a prominent place in the world economy. Unfortunately, information on this score contained in traditional and electronic publications is incomplete and insufficiently systematized, which limits people’s knowledge about Central Asia, lowers its investment attractiveness, and has a negative effect on the economic development of these countries. The purpose of this article is to furnish information about the potentialities of the Central Asian states in the world economy